BPHTB Management in Increasing Genuine Income Deli Serdang District - Rahmat Lubis; Bastari; Utary Maharany Barus; Maria (East Asian Journal of Multidisciplinary Research, 2022)
This research focuses on the role of land rent management (BPHTB). Increase in Regional Original Income (PAD) at the Regional Revenue Management Agency (BPPD) of Deli Serdang Regency. The problem of this research is the management of BPHTB with the increase of PAD in the BPPD of Deli Serdang Regency? The purpose of this study is to find out and analyze the management of BPHTB along with increasing PAD at BPPD Deli Serdang Regency in 2021. The method used in this research is a descriptive survey although the design used is a qualitative research design. research results etc. Data processing shows that managing the (BPHTB) in increasing local revenue (PAD) is quite helpful in increasing PAD.